2021
DOI: 10.1021/acs.orglett.1c02957
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ortho-Diamino-Functionalized 1-Arylnaphthalenes through Nickel-Catalyzed Cyclization of Ynamide-Benzylnitriles with Organoboronic Acids

Abstract: A nickel-catalyzed highly regioselective addition/cyclization of ynamide-benzylnitriles with organoboronic acids has been developed. The reaction offers an attractive route for the construction of diamino-functionalized 1-arylnaphthalenes, which is difficult to synthesize by other methods. In addition, a wide range of functional groups are tolerated in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…anti ‐Arylmetalative cyclization on specifically designed alkynes affords unusual architectures with cyclic endo ‐alkene derivatives [39–55] . In this realm, Tsukamoto group discovered the abnormal trans ‐addition of organoboronic reagents on alkynals and alkynones using palladium(0) catalyst [38] .…”
Section: Anti‐arylmetalative Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…anti ‐Arylmetalative cyclization on specifically designed alkynes affords unusual architectures with cyclic endo ‐alkene derivatives [39–55] . In this realm, Tsukamoto group discovered the abnormal trans ‐addition of organoboronic reagents on alkynals and alkynones using palladium(0) catalyst [38] .…”
Section: Anti‐arylmetalative Cyclizationmentioning
confidence: 99%
“…anti-Arylmetalative cyclization on specifically designed alkynes affords unusual architectures with cyclic endo-alkene derivatives. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In this realm, Tsukamoto group discovered the abnormal trans-addition of organoboronic reagents on alkynals and alkynones using palladium(0) catalyst. [38] The proposed mechanism involved oxidative addition without nucleometalation (without orthogonal activation of alkyne by Pd complex).…”
Section: Anti-arylmetalative Cyclizationmentioning
confidence: 99%
“…Very recently in 2021, Liu's group also developed the synthesis of ortho-diamino functionalized 1-arylnaphthalenes ( 52) via a Ni(II)-catalyzed regioselective addition/cyclization of ynamide-benzylnitriles (51) with organoboronic acids (Scheme 24). 42 This strategy provides an attractive route to access diamino-functionalized 1-arylnaphthalenes. The reaction proceeds through a regioselective β-addition of arylnickel species to the ynamide followed by cis-trans isomerization and, finally, a nucleophilic attack of the resulting alkenylmetal on the tethered nitrile group to afford the corresponding products.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…[5] In addition, selected examples of metal-assisted cyclization reaction via polarity inversion of CÀ C triple bond are fantastic addition to the ynamide chemistry. [6][7][8] Notably, Lam and Ye groups independently reported that reversal of CÀ C triple bond polarity in ynamides is possible by metal catalysts and arylboronic acids. [7] In another report, Sahoo group entrenched a gold(I)-catalyzed umpolung cycloisomerization of yne-teth-the background study, we realized that the chemistry of ynetethered ynamides is emerging but still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Of late, the asymmetric version of this reaction was developed by Marinetti, Arnold, and co‐workers [5] . In addition, selected examples of metal‐assisted cyclization reaction via polarity inversion of C−C triple bond are fantastic addition to the ynamide chemistry [6–8] . Notably, Lam and Ye groups independently reported that reversal of C−C triple bond polarity in ynamides is possible by metal catalysts and arylboronic acids [7] .…”
Section: Introductionmentioning
confidence: 99%